From Colonial Legacies to Contemporary Challenges: The Muslim Experience in Hong Kong and Macau - Li, Chun Leung; Isa, Khalid; Mustaffa, Khairul Anuwar; Lokman, Ainul Asyraf; Mohd Bakri, Mohamad Fikri (Journal of Al-Tamaddun, 2024)
This study explores the multifaceted challenges faced by the Muslim communities in Hong Kong and Macau, two cities characterized by their unique colonial histories and contemporary socio-economic dynamics. Despite the constitutional guarantee of religious freedom, Muslims in these regions encounter significant barriers to integration, including social prejudices, economic hardships, and limited access to educational resources. The objective of this research is to analyse these challenges and their implications for the Muslim population, utilizing a mixed-methods approach that combines qualitative interviews with quantitative data analysis. The findings reveal a persistent cycle of poverty exacerbated by misconceptions about Islam and cultural differences, highlighting the urgent need for targeted government interventions and community engagement strategies. This research underscores the importance of fostering ethnic harmony and enhancing the visibility of Muslim contributions to society, ultimately recommending a collaborative approach involving local authorities, community leaders, and educational institutions to promote inclusivity and understanding.